Impact of scientific conferences on climate change and how to make them eco-friendly and inclusive: A scoping review - Carl Froilan D. Leochico; Melina Longoni Di Giusto; Ramiro Mitre (Elsevier, 2021)
Scientific conferences are integral to all fields of study, providing learners of all ages with opportunities to improve their practices, resulting in advancements that may benefit the greater population. Traditionally, conferences are conducted in-person, entailing attendees to travel and consequently generate carbon dioxide. Aside from air travel that largely contributes to carbon emissions, conference-related equipment and accouterments and various activities related to travel can negatively impact the environment. Especially during the COVID-19 pandemic, the value of digitizing conferences through synchronous and/or asynchronous Internet-dependent techniques has been greatly recognized. Among the benefits of online or hybrid conferences, significant reductions in carbon footprint and various forms of waste (time, funds, resources, energy) are summarized in this scoping review. Based on the conference-related experiences from 11 included studies, this review also presents practical ways to organize eco-friendly and inclusive conferences, whether conducted in-person, online, or via a combination of both.